Secrets of the rock star programmers : riding the IT crest - Burns, Ed (McGraw-Hill, 2008)
A-list Programmers Reveal How to Develop Breakout Skills Find out what it takes to push your programming chops to the next level and design killer software by getting inside the minds of today's rock star programmers: {u2022} Rod Johnson, Inventor of the Spring Framework {u2022} Adrian Colyer, Pioneer of Aspect Oriented Programming Tools, Project Lead of AspectJ {u2022} Java Posse--Tor Norbye, Joe Nuxoll, Carl Quinn, and Dick Wall {u2022} Chris Wilson, Lead Architect of Microsoft Internet Explorer {u2022} Nikhil Kothari, Architect of ASP.NET AJAX {u2022} Hani Suleiman, Author of "The Bile Blog" {u2022} James Gosling, Father of Java {u2022} Kohsuke Kawaguchi, Creator of the Hudson Continuous Integration Tool {u2022} Herb Schildt, The World's Bestselling Programming Author {u2022} Floyd Marinescu, Co-founder of ServerSide.com; Founder and Lead Editor of InfoQ.com {u2022} Andy Hunt, Co-founder of the Pragmatic Programmers {u2022} Dave Thomas, Object Oriented Software Pioneer {u2022} Max Levchin, Co-founder and Former CTO of PayPal {u2022} Libor Michalek, Co-founder of Slide.com {u2022} Weird Al Yankovic, The Programmer's Rock Star.